A Morphological Stylistic Analysis of Song “I Wish I Hated You” by Ariana Grande - Mutiara Romi Artika; Vina Fitriani Dalimunte; Devi Sofilla; Rahmadsyah Rangkuti (LPPM Universitas Bumigora Mataram, 2024)
In societal interactions, language plays a fundamental role, serving crucial purposes. Language activities aim to express specific intentions and objectives. This study aims to examines Ariana Grande's song